Clinical outcome in two adult horses treated for cleft palate with laryngeal tie‐forward surgery. Issue 2 (4th June 2018) - Tosi, Irene; Grulke, Sigrid; Salciccia, Alexandra; de la Rebière de Pouyade, Geoffroy
Abstract : Two adult sport horses were referred for respiratory noise, exercise intolerance, coughing and nasal discharge containing food material. An asymmetrical, mild to moderate defect of the soft palate was diagnosed and surgically treated by laryngeal tie‐forward procedure (LTFP). The immediate postoperative endoscopic images were satisfactory; the epiglottis was in normal alignment, dorsal to the soft palate defect in both cases. When contacted respectively four months and three years after surgery, owners of both horses declared being satisfied with the outcome of surgery as initial clinical signs had reduced or disappeared. Follow‐up endoscopy showed some retraction of the larynx in both horses but the reduction of the palatal defect was adequate. This report demonstrates that horses can reach adulthood with certain soft palate defects and that severity of clinical signs varies between individuals. The authors suggest considering LTFP as an option in adult horses with small‐to‐moderate cleft palates causing clinical signs.